HUBUNGAN KERUGIAN EKONOMI DAN DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP PADA PASIEN HEMODIALISA DI RSUD BALARAJA - Rahmatulloh, Gilang; Sucipto, Sucipto; Iskandar, Arik (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2025)
ABSTRACTBackground Patients with kidney failure who undergo hemodialysis must go to hospital regularly and require non-medical costs such as transportation costs and others. This can definitely affect the patient's quality of life so that going to the hospital regularly and requiring non-medical care costs results in economic losses. Apart from that, it is important for chronic kidney failure patients undergoing hemodialysis to need family support to produce a good quality of life for the patient and prevent the occurrence of a poor quality of life for the patient which can affect the period of treatment in the hospital. The aim of this study was to determine the relationship between economic loss of family support and quality of life in hemodialysis patients. Research method is a quantitative research type with a descriptive cross sectional approach. The sample used was hemodialysis patients at Balaraja Regional Hospital, totaling 71 respondents. Research method is a quantitative research type with a descriptive cross sectional approach. The sample used was hemodialysis patients at Balaraja Regional Hospital, totaling 71 Respondents. Results Statistical test of the relationship between economic loss and quality of life in hemodialysis patients at Balaraja District Hospital with a P-Value of 0.012 0.05. There is a relationship between family support and quality of life in hemodialysis patients at Balaraja District Hospital with a P-Value of 0.011 0.05. Conclusion: In hemodialysis patients, economic losses and family support are related to quality of life. Nurses play an important role in providing support to patients and their families. Suggestions for future researchers could be to consider expanding the scope of the research by involving a more diverse population and sample, both in terms of age and geographical location. Future research is also recommended to explore other influencing factors such as stress levels, social support, or family parenting patterns. ABSTRAKLatar belakang Pasien gagal ginjal dengan menjalani hemodialisa harus rutin ke rumah sakit dan memerlukan biaya non medis seperti biaya transportasi dan lainnya , hal ini pasti dapat mempengaruhi kualitas hidup pasien sehingga dengan rutin ke rumah sakit dan memerlukan biaya non perawatan medis mengakibatkan terjadinya kerugian ekonomi. Selain itu pentingnya bagi pasien gagal ginjal kronik yang menjalani hemodialisa memerlukan dukungan keluarga untuk menghasilkan kualitas hidup pasien dengan baik dan mencegah terjadinya kualitas hidup passien yang buruk yang dapat mempengaruhi masa dalam pengobatannya di rumah sakit. Tujuan penelitian ini untuk mengetahui antara hubungan kerugian ekonomi dukungan keluarga dan kualitas hidup pada pasien hemodialisis. Metode Penelitian jenis penelitian kuantitatif dengan pendekatan cross sectional deskriptif sampel yang di gunakan adalah pasien hemodialisis di RSUD Balaraja sebanyak 71 responden. Hasil: adanya hubungan kerugian ekonomi dengan kualitas hidup pada pasien Hemodialisis Di RSUD Balaraja dengan nilai P-Value 0,012 0,05. adanya hubungan Dukungan keluarga dengan kualitas hidup pada pasien Hemodialisis Di RSUD Balaraja dengan nilai P-Value 0,011 0,05. Kesimpulan pada pasien hemodialisis, kerugian ekonomi dan dukungan keluarga berhubungan dengan kualitsa hidup. perawat memainkan peran penting dalam membrikan support kepada pasien dan keluarga mereka. Saran bagi peneliti selanjutnya dapat mempertimbangkan untuk memperluas cakupan penelitian dengan melibatkan populasi dan sampel yang lebih beragam, baik dari segi usia maupun lokasi geografis. Penelitian mendatang juga disarankan untuk mengeksplorasi faktor-faktor lain yang memengaruhi seperti tingkat stres, dukungan sosial, atau pola asuh keluarga